MAGISTER KEBIJAKAN PUBLIK DAN PEMBANGUNAN ERA OTSUS PAPUA - La Pona La Pona (JURNAL KEBIJAKAN PUBLIK, 2018)
Progress and problems of regional development in Papua special autonomy to the era, including the implications for public policy and the central government had made this region. Various public policies implemented since the former Dutch East Indies colony was integrated into the 1962's the Republic of Indonesia. A variety of public policy at the positive and negative implications for regional development and community development. Similarly, the 2001 special autonomy has also developed a variety of public policy. It is not known for certain whether public policies that have been through a process step that is true or not, according to the rules of science to public policy. Moreover, knowledge of public policy that is multi-disciplinary and inter-discipline can be said is a relatively new field of science in the curriculum of higher education in Indonesia. Until 2012 in Indonesia there are 5 (five) universities are here opened master in public policy sciences, and the fourth is Cenderawasih University by developing field of study Master (S2) of public policy at the beginning of 2012 which is the efforts of some academics in the field of development science and support the process of national development policies and the region